Effects of chromium addition on fatigue crack growth behavior of titanium aluminides - Ong, Wei Rex (2008)
The microstructure and fatigue crack growth behavior of various compositions of Ti-Al based intermatellics, Ti-48Al (at%), and the ternary alloys, Ti- 48Al-2Cr, Ti-48Al-4Cr and Ti-48Al-8Cr (at%) have been studied. The fatigue crack growth tests were performed on center-cracked-tension M(T) specimens at room temperature in laboratory air, subjected to a constant applied stress range 100MPa with a load ratio of minimum to maximum level, R = 0.1. It was found that the threshold of stress intensity factor range of Ti-48Al, Ti-48Al-2Cr, Ti-48Al-4Cr and Ti-48Al-8Cr are 12.0MPa v m, 9.0MPa v m, 8.0MPa v m and 4.5MPa v m respectively. The threshold of stress intensity factor range decreased with the increasing percentage of chromium added to Ti-48Al. The results also show that Ti- 48Al-2Cr has the highest fatigue crack resistance followed by Ti-48Al, Ti-48Al-4Cr and Ti48Al-8Cr. Field Emission Scanning Electron Microscopy (FESEM) technique was employed to investigate the fractography of each specimen after fatigue crack growth test. Micro-indentation tests results showed increasing hardness value of Ti- 48Al alloys when the chromium content increased. The microstructures of each type of Ti-48Al alloys were examined using optical and Scanning Electron Microscope (SEM). Finer laths of and plates in lamellar structure have been observed when the amount of chromium added in Ti-48Al increased. The effects of microstructure on fatigue crack growth of Ti-48Al alloys are discussed.